LA METAMORFOSI DEL MITO DI SCILLA - Ressel, Monica (Myrtia, 2000)
Figurative art and literature have been usually studied separately, without considering their possible interactions. The myth of Skylla offers an interesting example of how influences of sculpture and painting on texts and vice versa make the same story change. Among the numerous records of Skylla there is a striking gap dividing Homer's description and later elaboration. In the Odyssey Skylla is a threatening monster, a sort of gigantic octopus that lives in a cave; she has six long necks, twelve misshapen feet and cruel mouths with three rows of teeth. The vagueness of the description caused subsequent adulterations, because the creature was difficult to imagine and to reproduce in art. Skylla developed and became a charming and dangerous siren, who bit and gulped seamen with the three dog heads she had around her hips. As far as Homeric Skylla was perceived to be similar to other monsters, artists reduced her peculiar characteristics and new myths and new iconographic images aroused.